Pemanfaatan Umbi Gadung untuk Pengendalian Tikus di Desa Jatiwates Kecamatan Tembelang Jombang - Primaadi Airlangga; Ambar Susanti; Ainul Mu’arofati Zahro; Sopfi Hidayatul Choir; Winarti Wina (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
Utilization of Gadung Tubers (Dioscorea hispida) for Control of Rats, was carried out in Jatiwates Village, Tembelang District, Jombang Regency, from Octobe, 28 to Novembe, 08 2021. The partner for emporwerment community activities is the Farmers Group Association (GAPOKTAN) Jatiwates Village, Tembelang District. While the target audience is the farmers who are members of the farmer group as many as 25 participants. The objectives are; 1) provide information about the use of gadung tuber as raw material for controlling rat pests, 2) increase development in utilizing gadung tuber extract for controlling rats in food crops in Jatiwates Village, Tembelang District. The expected outputs are; 1) the farming community can know about the use of gadung tubers as raw material for controlling rat pests, 2) the use of gadung tuber extract for controlling rats, is expected to help and complete strategies for controlling rats to the maximum and reducing the impact of poisoning and environmental pollution. The results of the activity resulted in a fairly good difference in knowledge and skills after the target audience received socialization and training, namely 37% and 19%. The attitude towards the effectiveness of the rat birth control pill was around 15%. Further these implementation needs to be done in providing information and training on rat pest control strategies to farmers. In addition, testing the success of this rat birth control pill needs to be done, considering that environmental factors such as rainfall and stagnant water affect the effectiveness of giving birth control pills.